MANAJEMEN DATA DIGITAL DALAM MENCAPAI AKREDITASI UNGGUL DI MAS ISLAMIYAH SUNGGAL - Rizka Amanda Putri; Makmur Syukri (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the management of digital data in achieving excellent accreditation at MAS Islamiyah Sunggal. The focus of the study includes planning, implementation, obstacles, and solutions in digital data management carried out by the principal, operator, teachers, and administrative staff to support accreditation readiness. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results show that digital data management at MAS Islamiyah Sunggal has been carried out gradually and systematically through data collection, validation, storage, and continuous updating. This process is supported by clear division of tasks, internal coordination, and the use of digital information systems such as EMIS and accreditation support systems. The findings are in line with Terry’s view that management includes planning, organizing, actuating, and controlling, as well as Laudon and Laudon’s view that an effective information system must provide accurate, relevant, and timely data. However, this study also found several obstacles, such as the heavy workload of operators, the high level of accuracy required, and the lack of integration among several digital applications. In the perspective of Islamic education, these findings are relevant to Surah Al-Baqarah verse 282, which emphasizes the importance of proper, fair, and accountable recording.